Barriers to an inclusive academic library collection. (18th August 2021) - Price, Apryl C.
Abstract : Purpose: Libraries still endeavor to achieve diversity in many areas, including collections. Although many barriers to realizing this goal still exist, there are changes that can be made to improve the current situation. This paper aims to examine those barriers and discusses some ways librarians, administrators and publishers can help build inclusive academic library collections. Design/methodology/approach: This paper will discuss the issues that the University of North Florida's Thomas G. Carpenter Library discovered while trying to find ways to build a racially and ethnically diverse academic collection. Findings: The lack of diversity in academic library collections has many causes, including inadequate institutional collection priorities, librarian bias, heavy workloads and the dearth of diverse voices in the publishing industry. Originality/value: Diversity, equity and inclusion are key concepts to improving how libraries operate. However, libraries have struggled to realize this vision in many areas. This paper endeavors to identify ways academic librarians and publishers can make collections more diverse.